Ideas of Serbian enlighteners on creating a new concept of education - Kovačević Vesna G. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2019)
The Enlightenment concept of education in the Serbs began to develop late at the end of the 18th century. The Enlightenment concept of education was created and developed as an integral part of the humanisticenlightenment movement. Its basic source are philosophical and sociological ideas of many European enlighteners and advanced European thoughts. Such a concept was not genuine, but it was an epochal advance for Serbian pedagogy, school, and education. A great number of Serbian enlighteners tried to create a new concept of education. They believed in the unlimited powers of education and felt that only education could change society. The first Serbian educator and teacher St. Sava, the first Serbian rationalist Dositej Obradovic and an elite critic and reformer of the school, Vasa Pelagic, gave a special contribution to the constitution of the new concept of education. In this paper, the author presents the basic pedagogical ideas of Serbian enlighteners, the understanding of the essence of education and its goals as well as the views of the new school.